2007
DOI: 10.1002/jcp.21125
|View full text |Cite
|
Sign up to set email alerts
|

The chromatin of differentiating erythroblasts is cleaved into large size fragments independent of caspase activated DNase and apoptosis inducing factor

Abstract: Erythroblast cell differentiation involves self-controlled and limited nuclear proteolysis prior nucleus loss. Early evidence suggests that apoptotic-like pathways are activated during this process. The chromatin of developing erythroblasts becomes fragmented in vivo, however, the exact mechanisms and molecules involved remain elusive. In this study, erythroblasts were differentiated in culture from CD34-enriched umbilical cord blood progenitor cells and the characteristics of DNA fragmentation were examined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The TUNEL-positive DNA indicates cleavage by an endonuclease other than DNase II, since DNase II cleavage generates TUNEL-negative 3' phosphate ends. In the absence of the central macrophage, monocultures of hematopoietic stem cells differentiate into erythrocytes in a pathway that includes DNA fragmentation by a cell-autonomous endonuclease that generates 3'-OH DNA ends, as indicated by TUNEL positivity and large DNA fragments [11,27]. These data indicate that an unidentified cell-autonomous endonuclease(s) functions to initiate erythroblast DNA processing prior to macrophage engulfment and further degradation by DNase II.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…The TUNEL-positive DNA indicates cleavage by an endonuclease other than DNase II, since DNase II cleavage generates TUNEL-negative 3' phosphate ends. In the absence of the central macrophage, monocultures of hematopoietic stem cells differentiate into erythrocytes in a pathway that includes DNA fragmentation by a cell-autonomous endonuclease that generates 3'-OH DNA ends, as indicated by TUNEL positivity and large DNA fragments [11,27]. These data indicate that an unidentified cell-autonomous endonuclease(s) functions to initiate erythroblast DNA processing prior to macrophage engulfment and further degradation by DNase II.…”
Section: Discussionmentioning
confidence: 92%
“…Following engulfment of pyrenocytes, DNase II further degrades fragmented pyrenocyte DNA within macrophages [23,26]. The nuclease(s) that initiate cell-autonomous erythroblast genomic DNA degradation have yet to be identified, although it has been shown that caspase-activated DNase (CAD) is not involved [16,27]. The nucleases NM23-H1, apurinic/apyrimidinic endonuclease 1 (APE1) and TREX1, localize to the ER in the perinuclear space and might gain access to erythroblast nuclear DNA during the generation of transient openings in the nuclear membrane or membrane remodeling that segregates the ER to the pyrenocyte [16,24,27,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, an appreciation of the underlying biology that leads to the apparent difference in size between fetal and maternal cell-free DNA fragments could be useful. Accordingly, an understanding of syncytialization and trophoblast deportation may provide insight into the process whereby fetal cell-free fragments are generated (9 ), and investigations of erythroblast maturation and enucleation may shed new light on the nature of cell-free DNA in general (10 ). Such research may assist in unraveling the puzzle of cell-free DNA fragment size.…”
mentioning
confidence: 99%